ANALISIS KERENTANAN SOSIAL EKONOMI MASYARAKAT KECAMATAAN SEMARANG TENGAH TERHADAP PANDEMI COVID 19 - Sundaro, Hendrianto; Pamungkas, Wardana Galih (Jurnal Spasial, 2024)
Recently, the Government of Indonesia has revoked the status of the Covid 19 Pandemic. Even so, the pandemic event has sparked critical questions, “how can the city government prepare itself if in the future it is faced with a similar event? "Of course an analysis is needed to find out what factors have the most influence on the socio-economic vulnerability of the community to the Covid 19 pandemic and an overview of which locations are socially and economically vulnerable. With this analysis, the government can be better prepared when faced with similar events in the future.This study aims to determine the level of socio-economic vulnerability of the people in Central Semarang District to the Covid 19 Pandemic. The method used in this study is a quantitative method. Data obtained through observation, questionnaires and documentation studies. Data processing is carried out with the help of SPSS and Geographical Information System (GIS) programs. From the analysis that has been carried out, information is obtained that there are two dominant factors that influence the socio-economic vulnerability of the people in Central Semarang District, namely: the resilience factor and the social adaptation factor. In addition, information was also obtained that most of the villages in Central Semarang District had a relatively high level of socio-economic vulnerability, both in terms of resilience and adaptation factors.